(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article aims to use movement games as a means of physical education in the development of physical qualities in school-age children through the use of movement games, and on this basis to identify the theoretical foundations and methodological approaches to the technology of developing children’s movement activity in general secondary schools, and to organize and conduct research on the physical education and mass health activities carried out to develop children’s movement activity in general secondary schools in the process of achieving the goal.